2021
DOI: 10.1007/s10522-021-09944-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of the BNT162b2 mRNA COVID-19 vaccine in older residents of a long-term care facility: relation with age, frailty and prior infection status

Abstract: Clinical and biological assessment of the COVID-19 vaccine efficacy in the frail population is of crucial importance. The study focuses on measuring the levels of anti-SARS-CoV-2 IgG antibodies before and after BNT162b2 mRNA COVID-19 vaccination among long-term care facility (LTCF) elderly residents. We conducted a prospective, single-center, observational study among LTCF residents. The study protocol was based on three blood sample acquisitions: first taken at baseline—5 days before the first dose of the vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…The impact of frailty on COVID-19 vaccine outcomes has only been investigated without consideration of sex. Frailty does not impact vaccine-induced antibody responses against BNT162b2 when controlling for sex and other covariates ( Ríos et al, 2021 ) or when ignoring sex ( Demaret et al, 2021 ; Seiffert et al, 2021 ). Frailty does, however, increase the risk of post-vaccination infection when controlling for sex and age ( Antonelli et al, 2021 ; Hollinghurst et al, 2021 ).…”
Section: Introductionmentioning
confidence: 96%
“…The impact of frailty on COVID-19 vaccine outcomes has only been investigated without consideration of sex. Frailty does not impact vaccine-induced antibody responses against BNT162b2 when controlling for sex and other covariates ( Ríos et al, 2021 ) or when ignoring sex ( Demaret et al, 2021 ; Seiffert et al, 2021 ). Frailty does, however, increase the risk of post-vaccination infection when controlling for sex and age ( Antonelli et al, 2021 ; Hollinghurst et al, 2021 ).…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, studies investigating frailty have not found an effect on antibody responses [34][35][36], but have reported that frailty increases the risk of post-vaccination breakthrough infection [37,38], suggesting that the immunogenicity studies may have been under-powered to observe an effect of frailty or that lack of consideration of biological sex obscured the effect.…”
Section: Discussionmentioning
confidence: 99%
“…With antibody quantification, various studies verified that although the antibodies are present, there is a decrease in these antibodies. Pre-vaccination COVID-19 illness was the only factor associated with a lower rate of antibody decline at 6 months, while frailty, disability, older age, cognitive impairment, or comorbidity were not associated with the extent of antibody loss [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%